2014
DOI: 10.1111/bjep.12060
|View full text |Cite
|
Sign up to set email alerts
|

Growth trajectories of mathematics achievement: Longitudinal tracking of student academic progress

Abstract: Mathematics growth from Grade 6 to Grade 9 was slower than that from Grade 3 to Grade 6. Students with lower initial achievement improved at a faster rate than those who started at a higher level. Gender did not affect growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 68 publications
4
21
0
Order By: Relevance
“…This means that performance declines for girls and boys but that girls maintain their relative advantage. A similar developmental pattern for boys and girls is in line with the findings of research by Mok et al (2014) and Watt (2004), who did not find evidence for a gender intensification or gender convergence hypothesis. Watt (2004) observed an already existing difference between boys and girls at the start of their school career.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This means that performance declines for girls and boys but that girls maintain their relative advantage. A similar developmental pattern for boys and girls is in line with the findings of research by Mok et al (2014) and Watt (2004), who did not find evidence for a gender intensification or gender convergence hypothesis. Watt (2004) observed an already existing difference between boys and girls at the start of their school career.…”
Section: Discussionsupporting
confidence: 88%
“…Watt (2004) found no evidence for either a gender intensification or convergence hypothesis when focusing on mathematics and English self-perceptions, task values and task perceptions. Also, Mok et al (2014) found that gender did not affect the growth rate of mathematics scores on a vertically equated scale between grades 3, 6 and 9. Overall, research into the developmental patterns of adolescent boys' and girls' motivation and performance does not provide a clear hypothesis of performance trends.…”
Section: Moderators Of Development Of Student Performancementioning
confidence: 93%
“…The ELAC was calibrated for this study using a Rasch measurement model (Bond & Fox, 2007). The mathematics achievement was assessed by the Mathematics vertical scale developed by Lau and associates (Lau, Mok, & Yan, 2009 see also Mok, McInerney, Zhu, & Or, 2015). It comprises an item bank of over 2,500 items designed for the primary and secondary mathematics curricula in Hong Kong.…”
Section: Academic Achievementmentioning
confidence: 99%
“…While Ready () acknowledges the sophisticated development of measures of student growth, we still have a paucity of evidence examining the relationship between student achievement and overall achievement growth: That is, do students that achieve initial higher scores grow at a faster pace than lower‐achieving students? Therefore, sustained within‐person growth is increasingly important (Anderman et al ., ; Martin, , ; Martin & Liem, ; Mok, McInerney, Zhu, & Or, ). If we are to better understand growth for the individual student, researchers need more information on change over time, with an increased number of time points (that is more than two; Hedeker & Gibbons, ; McCoach, Madura, Rambo‐Hernandez, O'Connell, & Welsh, ; Raudenbush, ).…”
Section: Introductionmentioning
confidence: 99%